Epirubicin loading in poly(butyl cyanoacrylate) nanoparticles manifests via altered intracellular localization and cellular response in cervical carcinoma (HeLa) cells. (1st September 2016) - Evangelatov, Aleksandar; Skrobanska, Ralica; Mladenov, Nikola; Petkova, Milena; Yordanov, Georgi; Pankov, Roumen
Abstract: Objective : Drug loading into nanocarriers is used to facilitate drug delivery to target cells and organs. We have previously reported a change in cellular localization of epirubicin after loading to poly(butyl cyanoacrylate) (PBCA) nanoparticles. We aimed to further investigate the altered cellular localization and cellular responses to the described drug formulation. Materials and methods : HeLa cells were treated with epirubicin-loaded PBCA nanoparticles prepared by the pre-polymerization method. A systematic study was performed to evaluate the formulation cytotoxicity. Cellular localization and uptake of the formulation as well as cellular response to the treatment were evaluated. Results : Our studies revealed decreased cytotoxicity of the nanoparticle-formulated epirubicin compared to the free drug as well as a noticeable change in the drug's intracellular localization. Epirubicin-loaded nanoparticles were internalized via endocytosis, accumulated inside endosomal vesicles and induced a two-fold stronger pro-apoptotic signal when compared to the free drug. The level of the tumor suppressor protein p53 in HeLa cells increased significantly upon treatment with free epirubicin, but remained relatively unchanged when cells were treated with equivalent dose of nanoparticle-loaded drug, suggesting a possible shift from p53-dependent DNA/RNA intercalation-based induction of cytotoxicity by free epirubicin to a caspase 3-induced cell death by the epirubicin-loaded PBCA formulation.